Faktor Yang Berhubungan Dengan Stres Kerja Pada Pekerja Bagian Finishing Di Proyek Rumah Sakit UPT Vertikal Makassar - Dea Sintya Ananda; Yuliati; Nur Ulmy Mahmud (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
The World Health Organization (WHO) reports that more than half of workers in developed countries experience work stress in the workplace. Nearly 11 million people suffer from work stress in the United States, and it is said that work stress is the most important problem in life. Many factors can trigger stressful situations for workers, namely heavy workloads, poor interpersonal relationships between employees, uncomfortable work environments, or lack of work facilities. This study aims to determine the relationship between work stress, workload, and psychosocial and interpersonal relationships in finishing workers at the UPT Vertical Makassar Hospital Project. The type of research used in this study is quantitative research using a cross-sectional approach. The sampling technique in this study is simple random sampling. The population in this study consisted of finishing workers at the UPT Vertical Makassar Hospital Project, totaling 200 people and a sample size of 133 people. Data were obtained using a questionnaire. The analysis method used was univariate and bivariate analysis using the chi-square test. This study's results indicate a relationship between workload and work stress (p-value = 0.028 <0.05%). There is no psychosocial relationship with work stress (p-value = 0.837 > 0.05%). There is an interpersonal relationship with work stress (p-value = 0.000 <0.05%). From the results of this study, the researcher found that there are still workers who experience work stress, so it is hoped that the company will pay more attention to its workers to reduce work stress through workload adjustments. It is hoped that the company will also maintain a family attitude so that workers do not have disagreements and provide social support so as not to cause mental burdens that can cause work stress, which can produce high productivity and improve the quality of work.